Colonial Odysseys : Empire and Epic in the Modernist Novel - Adams, David, 1959- (Book collections on Project MUSE., 2003)
Works such as Joseph Conrad's Heart of Darkness and Lord Jim, Virginia Woolf's The Voyage Out, E. M. Forster's A Passage to India, and Evelyn Waugh's A Handful of Dust explore the relationship between Britain and its colonies when the British Empire was at its height. David Adams observes that, because of their structure and specific literary allusions, they also demand to be read in relation to the epic tradition. The elegantly written and powerfully argued Colonial Odysseys focuses on narratives published in English between 1890 and 1940 in which protagonists journey from the familiar world of Europe to alien colonial worlds. The underlying concerns of these narratives, Adams discovers, are often less political or literary than metaphysical: in each of these fictions a major character dies as a result of the journey, inviting reflection on the negation of existence. Repeatedly, imaginative encounters with distant, uncanny colonies produce familiar, insular presentations of life as an odyssey, with death as the home port. Expanding postcolonial and Marxist theories by drawing on the philosophy of Hans Blumenberg, Adams finds in this preoccupation with mortality a symptom of the failure of secular culture to give meaning to death. This concern, in his view, shapes the ways modernist narratives reinforce or critique imperial culture-the authors project onto British imperial experience their anxieties about the individual's relation to the absolute.